DESIGN AND EFFICIENCY ANALYSIS OF MINI SOLAR PANELS FOR POWER BANKS - Marisa, Putri; Aulia Nanda, Rizki; Taufik Ulhakim, Muhamad (JTH: Journal of Technology and Health, 2024)
The rapid development of science and technology has had a significant impact on today's global society. One of the fastest-growing technologies is mobile phones, which have an important component: the battery. Without a battery, a mobile phone cannot function as a communication device. This research develops a solar-powered mini power bank, The purpose of this research is the design of a mini solar panel power bank, the process of charging and using a mini solar panel power bank, and the efficiency produced by the mini solar panel power bank. The research conducted uses the design and analysis method of mini solar panels for power banks. The stages of this research are divided into four parts, namely the design of mini solar panels, the process of making mini solar panels, and the design of acrylic shapes. The device is designed with two solar panels connected in parallel, producing a maximum voltage of 24 V and a power of 3.0 W. The system includes a battery, a USB DC to DC step-down charging module, an adjustable module for increased battery charging, and an Arduino UNO R3, enclosed in an acrylic case measuring 20 cm x 12.5 cm x 6 cm. The solar panel is connected to the battery charging upgrade step-up module, which then supplies power to the battery, resulting in an output to the USB port. During a charging time of 180 minutes, the average power output of the solar panel is 2.00 W, while the battery produces an average of 0.477 W, with a mobile phone charging efficiency of 0.513 W in 90 minutes, resulting in an efficiency difference of 20.70%. This solar-powered power bank provides a backup power solution for communication devices, especially beneficial for those traveling to areas far from PLN's electricity range.